TaHfC-SiC ceramic coating based on carbon-based composite material and preparation method of TaHfC-SiC ceramic coating

By introducing SiC into the ultra-high temperature ceramic coating and forming an embedded interlocking structure, the problems of low binding strength and easy cracking caused by the difference in thermal expansion coefficient between TaHfC and carbon-based composite materials are solved, and higher binding strength and oxidative ablation resistance are achieved.

CN119528608APending Publication Date: 2025-02-28BEIJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411725202.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing ultra-high temperature ceramic coatings have a large gap in thermal expansion coefficients between TaHfC and carbon-based composite materials, resulting in low bond strength and easy cracking.

Method used

The preparation method of TaHfC-SiC ceramic coating based on carbon-based composite materials is adopted. By mixing TaHfC ceramic powder, Si powder and C powder ball mill, an embedded powder is obtained, and then the carbon-based composite material is embedded and sintered to generate SiC and form an embedded interlocking structure, which improves the binding strength and reduces the risk of cracking caused by the difference in thermal expansion coefficient.

Benefits of technology

The firm combination of TaHfC-SiC ceramic coating and carbon-based composite materials is achieved, reducing the risk of cracking and improving the oxidation and ablation resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention provides a TaHfC-SiC ceramic coating based on a carbon-based composite material and a preparation method of the TaHfC-SiC ceramic coating, and belongs to the technical field of ultrahigh-temperature ceramic coatings. The preparation method comprises the following steps: ball-milling and mixing TaHfC ceramic powder, Si powder and C powder to obtain embedding powder, then embedding and sintering a carbon-based composite material to obtain a TaHfC-SiC ceramic coating based on the carbon-based composite material, and enabling Si in the embedding powder to react with C in the embedding powder and C in the carbon-based composite material to generate SiC, so that the carbon-based composite material can be prepared into the TaHfC-SiC ceramic coating based on the carbon-based composite material. And the risk of cracking between the TaHfC and the carbon-based composite material due to overlarge difference of thermal expansion coefficients is reduced. The TaHfC-SiC ceramic coating based on the carbon-based composite material provided by the invention is uniform and crack-free after being examined by oxyacetylene flame at the temperature of 2200 DEG C for 120 seconds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultra-high temperature ceramic coatings, and in particular to a TaHfC-SiC ceramic coating based on a carbon-based composite material and a preparation method thereof. Background Art

[0002] Ultra-high temperature ceramic materials mainly refer to a special material that can maintain chemical stability in high temperature environments (above 2000°C) and reaction atmospheres (such as atomic oxygen environments), usually including some high-melting point transition metal compounds such as borides, carbides, and oxides; while ultra-high temperature ceramic coatings refer to the preparation of ultra-high temperature ceramic materials in the form of coatings on the surface of carbon-based composite materials. This coating has comprehensive properties such as extremely high temperature resistance, oxidation resistance, and long life, and is one of the key technologies for new aerospace vehicles. Among these high-melting point transition metal compounds, TaC and HfC are both NaCl face-centered cubic structures. The solid solution TaHfC formed by the two has a high melting point and is often used to prepare ultra-high temperature ceramic coatings. However, the ultra-high temperature ceramic coatings currently prepared are prone to cracking due to the large difference in thermal expansion coefficients between TaHfC and carbon-based composite materials and low bonding strength. Summary of the invention

[0003] The purpose of the present invention is to provide a TaHfC-SiC ceramic coating based on a carbon-based composite material and a preparation method thereof. The TaHfC-SiC ceramic coating based on a carbon-based composite material prepared by the present invention is not prone to cracking.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a TaHfC-SiC ceramic coating based on a carbon-based composite material, comprising the following steps:

[0006] (1) ball milling a raw material powder to obtain an embedded powder; the raw material powder comprises TaHfC ceramic powder, Si powder and C powder;

[0007] (2) embedding the carbon-based composite material into the embedding powder obtained in step (1) and sintering the embedded powder to obtain a TaHfC-SiC ceramic coating based on the carbon-based composite material.

[0008] Preferably, in step (1), the particle size of the TaHfC ceramic powder is 1 to 3 μm.

[0009] Preferably, the method for preparing the TaHfC ceramic powder comprises: ball milling and sintering Ta2O5 powder, HfO2 powder and C powder in sequence to obtain TaHfC ceramic powder.

[0010] Preferably, the mass content of TaHfC ceramic powder in the raw material powder in step (1) is 30-40% of the mass of the raw material powder.

[0011] Preferably, the mass content of Si powder in the raw material powder in step (1) is 40-50% of the mass of the raw material powder.

[0012] Preferably, the mass content of C powder in the raw material powder in step (1) is 5-10% of the mass of the raw material powder.

[0013] Preferably, in step (1), the rotation speed of the ball mill is 300-500 r / min, the ball milling time is 4-6 h, and the ball milling medium is anhydrous ethanol.

[0014] Preferably, in step (2), the sintering temperature is 1600-1800° C., and the sintering time is 1-3 hours.

[0015] Preferably, the sintering in step (2) is pressureless sintering, and the sintering atmosphere is an inert atmosphere.

[0016] The present invention also provides TaH based on carbon-based composite material prepared by the preparation method described in the above technical solution f C-SiC ceramic coating, comprising a carbon-based composite material and TaH in-situ generated on the surface of the carbon-based composite material f C-SiC ceramic coating.

[0017] The present invention provides a method for preparing a TaHfC-SiC ceramic coating based on a carbon-based composite material, comprising the following steps: (1) ball-milling a raw material powder to obtain an embedding powder; the raw material powder comprises TaHfC ceramic powder, Si powder and C powder; (2) embedding a carbon-based composite material in the embedding powder obtained in step (1) and sintering the embedded powder to obtain a TaHfC-SiC ceramic coating based on the carbon-based composite material. The present invention obtains an embedding powder by ball-milling TaHfC ceramic powder, Si powder and C powder, and then embeds and sinters the carbon-based composite material to obtain a TaHfC-SiC ceramic coating based on a carbon-based composite material, wherein Si in the embedding powder reacts with C in the embedding powder and C in the carbon-based composite material to generate SiC, and a TaHfC-SiC ceramic coating is generated in situ on the surface of the carbon-based composite material, forming an embedded interlocking structure at the interface, forming a strong bond with the carbon-based composite material, thereby improving the bonding strength between the TaHfC-SiC ceramic coating and the carbon-based composite material; and the thermal expansion coefficient of SiC is between TaHfC and the carbon-based composite material, thereby reducing the risk of cracking between TaHfC and the carbon-based composite material due to the large difference in thermal expansion coefficient. The results of the embodiment show that after the TaHfC-SiC ceramic coating based on the carbon-based composite material provided by the present invention is tested at 2200°C for 120s by an oxyacetylene flame, the coating is uniform and has no cracks, and the mass ablation rate of the coating is 8.3×10 -4 g / s, the linear ablation rate is 1.5×10 -4 mm / s. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The Ta prepared in Example 1 0.8 Hf 0.2 C SEM image of ceramic powder;

[0019] Figure 2 The Ta prepared in Example 1 0.8 Hf 0.2 C EDS image of ceramic powder;

[0020] Figure 3 The Ta prepared in Example 1 0.8 Hf 0.2 C XRD pattern of ceramic powder;

[0021] Figure 4 The Ta based carbon-based composite material obtained in Example 1 0.8 Hf 0.2 Surface SEM image of C-SiC ceramic coating;

[0022] Figure 5 The Ta based carbon-based composite material obtained in Example 1 0.8 Hf 0.2Cross-sectional SEM image of C-SiC ceramic coating;

[0023] Figure 6 The Ta based carbon-based composite material obtained in Example 1 0.8 Hf 0.2 Macroscopic morphology of C-SiC ceramic coating after ablation test;

[0024] Figure 7 The Ta based carbon-based composite material obtained in Example 1 0.8 Hf 0.2 Ablation test curve of C-SiC ceramic coating;

[0025] Figure 8 The Ta based carbon-based composite material obtained in Example 1 0.8 Hf 0.2 Cross-sectional SEM image of C-SiC ceramic coating after ablation;

[0026] Fig. 9 This is a macroscopic morphology of the TaC-20mol% HfC-SiC coating based on the carbon-based composite material obtained in Comparative Example 1 after ablation assessment;

[0027] Fig.10 This is a surface SEM image of the TaC-20mol% HfC-SiC coating based on the carbon-based composite material obtained in Comparative Example 1 after ablation assessment;

[0028] Fig.11 This is a cross-sectional SEM image of the TaC-20mol% HfC-SiC coating based on the carbon-based composite material obtained in Comparative Example 1 after ablation assessment. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing a TaHfC-SiC ceramic coating based on a carbon-based composite material, comprising the following steps:

[0030] (1) ball milling a raw material powder to obtain an embedded powder; the raw material powder comprises TaHfC ceramic powder, Si powder and C powder;

[0031] (2) embedding the carbon-based composite material into the embedding powder obtained in step (1) and sintering the embedded powder to obtain TaH based on the carbon-based composite material. f C-SiC ceramic coating.

[0032] The invention ball-mills the raw material powder to obtain the embedding powder.

[0033] In the present invention, the raw material powder includes TaHfC ceramic powder, Si powder and C powder. The present invention uses TaHfC ceramic powder as a raw material with a high melting point and strong anti-oxidation and ablation properties. Si powder can react with C in the embedding powder and C in the carbon-based composite material to generate SiC, whose thermal expansion coefficient is between TaHfC and the carbon-based composite material, thereby reducing the risk of cracking between TaHfC and the carbon-based composite material due to excessive difference in thermal expansion coefficient.

[0034] In the present invention, the TaHfC ceramic powder is preferably Ta 0.8 Hf 0.2 C. The present invention limits the type of TaHfC ceramic powder to ensure that the prepared TaHfC-SiC ceramic coating based on carbon-based composite materials can generate HfO2 and Ta2O5 in situ during the anti-oxidation ablation process, and the two can react to generate high-melting-point Hf6Ta2O 17 ; and HfO2 and Hf6Ta2O 17 The coupled synergistic effect can pin Ta2O5 in situ to achieve the sealing of cracks and holes, thereby making the TaHfC-SiC ceramic coating based on carbon-based composite materials more resistant to oxidation and ablation.

[0035] In the present invention, the particle size of the TaHfC ceramic powder is preferably 1-3 μm; in an embodiment of the present invention, the particle size of the TaHfC ceramic powder can be specifically 1 μm, 2 μm or 3 μm. The present invention limits the particle size of the TaHfC ceramic powder to ensure that it can be mixed more evenly with other raw materials.

[0036] In the present invention, the method for preparing the TaHfC ceramic powder preferably comprises: ball milling and sintering Ta2O5 powder, HfO2 powder and C powder in sequence to obtain TaHfC ceramic powder.

[0037] In the present invention, the particle size of the Ta2O5 powder is preferably 0.5 to 3 μm; in an embodiment of the present invention, the particle size of the Ta2O5 powder can be specifically 0.5 μm, 1 μm, 2 μm or 3 μm. The present invention limits the particle size of the Ta2O5 powder to ensure that it can be mixed more evenly with other raw materials.

[0038] In the present invention, the particle size of the HfO2 powder is preferably 0.5 to 3 μm; in an embodiment of the present invention, the particle size of the HfO2 powder can be specifically 0.5 μm, 1 μm, 2 μm or 3 μm. The present invention limits the particle size of the HfO2 powder to ensure that it can be mixed more evenly with other raw materials.

[0039] In the present invention, the particle size of the C powder is preferably 200-500 mesh; in the embodiment of the present invention, the particle size of the C powder can be specifically 200 mesh, 300 mesh, 400 mesh or 500 mesh. The present invention limits the particle size of the C powder to ensure that it can be mixed more evenly with other raw materials.

[0040] In the present invention, the mass ratio of the Ta2O5 powder, HfO2 powder and C powder is preferably calculated according to the ratio of the amount of each element in the TaHfC ceramic powder. 0.8 Hf 0.2 When the C ceramic powder is used, the mass ratio of the Ta2O5 powder, the HfO2 powder and the C powder is 73.6:35:1.

[0041] In the present invention, the ball milling method of the Ta2O5 powder, HfO2 powder and C powder is preferably wet ball milling. In the present invention, the medium of the ball milling is preferably anhydrous ethanol. In the present invention, the mass ratio of the anhydrous ethanol to the raw material is preferably (3-4):1; in an embodiment of the present invention, the mass ratio of the anhydrous ethanol to the raw material may be specifically 3:1 or 4:1. In the present invention, the grinding balls of the ball milling are preferably zirconia ball milling beads. In the present invention, the diameter of the zirconia ball milling beads is preferably 2mm, 5mm and 8mm. As an embodiment, the mass ratio of the 2mm, 5mm and 8mm zirconia ball milling beads may be (1-2.1): (1.5-2.1): 1; in an embodiment of the present invention, the mass ratio of the 2mm, 5mm and 8mm zirconia ball milling beads may be specifically 1:1.5:1, 1:2:1, 1.5:2:1 or 2:2:1. In the present invention, the ball-to-material ratio of the ball mill is preferably 8:(4.5-5.5); in an embodiment of the present invention, the ball-to-material ratio of the ball mill can be specifically 8:4.5, 8:5 or 8:5.5. In the present invention, the rotation speed of the ball mill is preferably 300-500r / min; in an embodiment of the present invention, the rotation speed of the ball mill can be specifically 300r / min, 350r / min, 400r / min, 450r / min or 500r / min. In the present invention, the ball milling time is preferably 1-3h; in an embodiment of the present invention, the ball milling time can be specifically 1h, 2h or 3h. The present invention limits the ball milling method and parameters of Ta2O5 powder, HfO2 powder and C powder to ensure more uniform mixing of raw materials, which is conducive to more sufficient generation of subsequent TaHfC ceramic powder.

[0042] After the ball milling is completed, the present invention preferably removes the ball milling medium and then performs sintering, and the method of removing the medium is preferably drying. As an embodiment, the drying temperature can be 80 to 100°C; in an embodiment of the present invention, the drying temperature can be specifically 80°C, 90°C or 100°C. As an embodiment, the drying time can be 8 to 12 hours; in an embodiment of the present invention, the drying time can be specifically 8 hours, 9 hours, 10 hours, 11 hours or 12 hours.

[0043] In the present invention, the sintering is preferably pressureless sintering. In the present invention, the reaction occurring during the sintering process is preferably Ta2O5(s)+HfO2(s)+C(s)=TaHfC(s)+6CO(g). In the present invention, the sintering temperature is preferably 1700~1800℃; in an embodiment of the present invention, the sintering temperature may be specifically 1700℃, 1750℃ or 1800℃. In the present invention, the sintering time is preferably 1~3h; in an embodiment of the present invention, the sintering time may be specifically 1h, 2h or 3h. As an embodiment, the heating rate of the sintering may be 5~10℃ / min; in an embodiment of the present invention, the heating rate of the sintering may be specifically 5℃, 6℃, 7℃ / min, 8℃ / min, 9℃ / min or 10℃ / min. In the present invention, the sintering is preferably carried out under an argon atmosphere. The present invention limits the sintering parameters to ensure that the raw materials react more fully to obtain TaHfC ceramic powder with a smaller particle size.

[0044] Compared with the prior art, the TaHfC ceramic powder prepared by the preparation method of the present invention can realize low-temperature pressureless sintering of the TaHfC ceramic powder without adding a sintering aid, and the prepared TaHfC ceramic powder has good density and uniform distribution of atoms.

[0045] In the present invention, the particle size of the Si powder is preferably 200-500 mesh; in the embodiment of the present invention, the particle size of the Si powder can be specifically 200 mesh, 300 mesh, 400 mesh or 500 mesh. The present invention limits the particle size of the Si powder to ensure that it can be mixed more evenly with other raw materials.

[0046] In the present invention, the particle size of the C powder is preferably 200-500 mesh; in the embodiment of the present invention, the particle size of the C powder can be specifically 200 mesh, 300 mesh, 400 mesh or 500 mesh. The present invention limits the particle size of the C powder to ensure that it can be mixed more evenly with other raw materials.

[0047] In the present invention, the TaH f The mass content of the C ceramic powder is preferably 30-40%. In the embodiment of the present invention, the TaHf The mass content of the C ceramic powder can be specifically 30%, 35% or 40%. f The mass content of C ceramic powder is to fully avoid TaH f The C ceramic powder is in direct contact with the carbon-based composite material, so that the prepared TaHfC-SiC ceramic coating based on the carbon-based composite material is not easy to crack.

[0048] In the present invention, the mass content of Si powder in the raw material powder is preferably 40-50%; in the embodiment of the present invention, the mass content of Si powder in the raw material powder can be specifically 40%, 45% or 50%. The present invention limits the mass content of Si powder in the raw material powder to ensure that Si reacts more fully with C in the embedding powder and C in the carbon-based composite material during the sintering process to generate a thermal expansion coefficient between TaH f C and SiC between carbon-based composites, reducing TaH f The risk of cracking due to the large difference in thermal expansion coefficient between C and carbon-based composites is reduced, and a stronger bond with carbon-based composites is achieved.

[0049] In the present invention, the mass content of C powder in the raw material powder is preferably 5-10%; in the embodiment of the present invention, the mass content of C powder in the raw material powder can be specifically 5%, 8% or 10%. The present invention limits the mass content of C powder in the raw material powder to ensure that during the sintering process, excess Si can react more fully with C in the embedding powder and with C in the carbon-based composite material, thereby in-situ generating a TaHfC-SiC coating on the surface of the carbon-based composite material.

[0050] In the present invention, the ball milling of the raw material powder is preferably the same as the ball milling method, ball milling media, grinding balls, ball-to-material ratio and ball milling speed in the above-mentioned method for preparing TaHfC ceramic powder, which will not be repeated here. As an embodiment, the ball milling time of the raw material powder can be 4 to 6 hours; in an embodiment of the present invention, the ball milling time can be specifically 4 hours, 5 hours or 6 hours. The present invention limits the ball milling time to ensure that the TaHfC ceramic powder, Si powder and C powder are mixed more evenly.

[0051] After the ball milling is completed, the present invention preferably removes the ball milling medium to obtain the embedded powder. In the present invention, the method of removing the ball milling medium is the same as the operation in the above-mentioned method for preparing TaHfC ceramic powder, which will not be repeated here.

[0052] After the embedding powder is obtained, the present invention embeds the carbon-based composite material into the embedding powder and sintering is performed to obtain a TaHfC-SiC ceramic coating based on the carbon-based composite material.

[0053] In the present invention, the carbon-based composite material is preferably 2.5D woven with a density of 1.5 g / cm 3 The present invention limits the types of carbon-based composite materials to ensure better matching with the thermophysical properties of SiC.

[0054] In the present invention, embedding the carbon-based composite material into the obtained embedding powder can ensure that the subsequently prepared TaHfC-SiC ceramic coating uniformly covers all parts of the carbon-based composite material and ensures that the TaHfC-SiC ceramic coating and the carbon-based composite material have good interface bonding strength.

[0055] In the present invention, the thickness of the embedded powder covered on the carbon-based composite material is preferably 1 to 3 mm; in an embodiment of the present invention, the amount of embedded powder covered on the carbon-based composite material can be specifically 1 mm, 2 mm or 3 mm. The present invention limits the amount of coverage per unit area of ​​the carbon-based composite material to ensure that the thickness of the TaHfC-SiC ceramic coating based on the carbon-based composite material is more uniform.

[0056] In the present invention, the sintering is preferably pressureless sintering. In the present invention, during the sintering process, TaH f The Si in the C-SiC embedding powder reacts with the C in the embedding powder and the C in the carbon-based composite material to form SiC, whose thermal expansion coefficient is between TaHfC and the carbon-based composite material, thereby reducing the thermal expansion coefficient of TaHfC. f The risk of cracking due to the large difference in thermal expansion coefficient between C and carbon-based composites.

[0057] In the present invention, the sintering temperature is preferably 1600-1800°C; in an embodiment of the present invention, the sintering temperature may be specifically 1600°C, 1650°C, 1700°C, 1750°C or 1800°C. In the present invention, the sintering time is preferably 1-3h; in an embodiment of the present invention, the sintering time may be specifically 1h, 2h or 3h. In the present invention, the heating rate of the sintering is preferably 5-10°C / min; in an embodiment of the present invention, the heating rate of the sintering may be specifically 5°C, 6°C, 7°C / min, 8°C / min, 9°C / min or 10°C / min. In the present invention, the sintering is preferably carried out under an argon atmosphere. The present invention limits sintering parameters to ensure that Si in the embedding powder reacts more fully with C in the embedding powder and C in the carbon-based composite material to generate SiC, generates a TaHfC-SiC ceramic coating in situ on the surface of the carbon-based composite material, forms an embedded interlocking structure at the interface, forms a firm bond with the carbon-based composite material, and further improves the bonding strength between the TaHfC-SiC ceramic coating and the carbon-based composite material; and the thermal expansion coefficient of SiC is between that of TaHfC and the carbon-based composite material, thereby reducing the risk of cracking between TaHfC and the carbon-based composite material due to excessive difference in thermal expansion coefficients, thereby further improving the bonding strength between TaHfC and the carbon-based composite material, and limits the sintering parameters to ensure that the thickness of the prepared TaHfC-SiC ceramic coating based on the carbon-based composite material is more uniform.

[0058] The present invention obtains TaHfC-SiC embedding powder by ball-milling and mixing TaHfC ceramic powder, Si powder and C powder, and then embeds and sinters the carbon-based composite material to obtain a TaHfC-SiC ceramic coating based on the carbon-based composite material, so that Si in the TaHfC-SiC embedding powder reacts with C in the embedding powder and C in the carbon-based composite material to generate SiC, whose thermal expansion coefficient is between that of TaHfC and the carbon-based composite material, thereby reducing the TaHfC-SiC ceramic coating. f The risk of cracking due to the large difference in thermal expansion coefficient between C and carbon-based composites.

[0059] The present invention also provides TaH based on carbon-based composite material prepared by the preparation method described in the above technical solution f C-SiC ceramic coating, comprising a carbon-based composite material and TaH in-situ generated on the surface of the carbon-based composite material f C-SiC ceramic coating.

[0060] In the present invention, the TaHfC is preferably Ta 0.8 Hf 0.2 C. In the present invention, the Ta in the TaHfC-SiC ceramic coating 0.8 Hf 0.2C can generate HfO2 and Ta2O5 in situ during the oxidation resistance ablation process, and the two can react to generate Hf6Ta2O with high melting point. 17 ; and HfO2 and Hf6Ta2O 17 The coupled synergistic effect can pin Ta2O5 in situ to achieve the filling of cracks and holes, making the TaHfC-SiC ceramic coating more resistant to oxidation and ablation, thereby improving the anti-oxidation and ablation properties of carbon-based composites.

[0061] In the present invention, the SiC is preferably generated by the reaction of Si and C in the embedding powder and Si in the embedding powder and C in the carbon-based composite material. In the present invention, the SiC in the TaHfC-SiC ceramic coating forms an embedded interlocking structure at the interface between TaHfC and the carbon-based composite material, ensuring that the carbon-based composite material can be firmly combined with the carbon-based composite material in the subsequent anti-oxidation ablation process and is not easy to crack.

[0062] In the present invention, the thickness of the TaHfC-SiC ceramic coating based on the carbon-based composite material may be 150 to 190 μm; in an embodiment of the present invention, the thickness of the TaHfC-SiC ceramic coating based on the carbon-based composite material may be specifically 150 μm, 160 μm, 170 μm, 180 μm or 190 μm. The present invention limits the thickness of the TaHfC-SiC ceramic coating based on the carbon-based composite material to ensure that the TaHfC-SiC ceramic coating based on the carbon-based composite material is f C-SiC ceramic coating has better resistance to oxidation and ablation and is more stable and does not crack during oxidation and ablation.

[0063] The TaHfC-SiC ceramic coating based on the carbon-based composite material prepared by the present invention is uniform and has no cracks after being tested at 2200° C. by an oxyacetylene flame for 120 seconds.

[0064] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] Example 1

[0066] A method for preparing a TaHfC-SiC ceramic coating based on a carbon-based composite material comprises the following steps:

[0067] (1) Ta with a particle size of 1 to 3 μm and a mass content of 30% 0.8 Hf 0.2C ceramic powder, Si powder with a particle size of 200 mesh and a mass content of 50%, and C powder with a particle size of 200 mesh and a mass content of 8% were mixed with anhydrous ethanol, and then ball-milled in a stirring ball mill at a speed of 300 r / min for 6 h, and then dried in an oven at 80°C for 12 h to obtain TaH f C-SiC embedding powder; the mass ratio of anhydrous ethanol to raw material powder is 3:1; the ball mill is zirconia ball milling beads; the diameters of the zirconia ball milling beads are 2mm, 5mm and 8mm respectively; the mass ratio of the 2mm, 5mm and 8mm zirconia ball milling beads is 1:2:1; the ball-to-material ratio is 8:5;

[0068] The Ta 0.8 Hf 0.2 The preparation method of C ceramic powder consists of the following steps:

[0069] Follow 0.8 Hf 0.2 The corresponding Ta2O5 powder with a particle size of 500nm, HfO2 powder with a particle size of 500nm and C powder with a particle size of 200 mesh were weighed in accordance with the ratio of the amount of each element in C, and ball milled and sintered in sequence to obtain TaHfC ceramic powder; the ball milling time was 3h, and the other ball milling parameters were the same as the ball milling parameters for preparing TaHfC-SiC embedded powder mentioned above; the sintering was performed by placing the ball-milled raw materials in a graphite crucible, heating to 1800℃ at 10℃ / min in an argon atmosphere, and pressurelessly sintering for 3h.

[0070] (2) The carbon-based composite material is embedded in the TaHfC-SiC embedding powder obtained in step (1), and then placed in a graphite crucible, heated to 1800° C. at 10° C. / min in an argon atmosphere, and pressurelessly sintered for 3 h to obtain a TaHfC-SiC ceramic coating based on the carbon-based composite material with a thickness of 170±20 μm.

[0071] Comparative Example 1

[0072] A method for preparing a TaC-20mol% HfC-SiC ceramic coating based on a carbon-based composite material, comprising the following steps:

[0073] (1) A TaC powder with a particle size of 1 to 3 μm and a mass content of 24.1%, a HfC powder with a particle size of 500 nm and a mass content of 5.9%, a Si powder with a particle size of 200 mesh and a mass content of 55%, and a C powder with a particle size of 200 mesh and a mass content of 8% are mixed with anhydrous ethanol, and then ball-milled in a stirring ball mill at a speed of 300 r / min for 6 hours, and then dried in an oven at 80° C. for 12 hours to obtain TaC-20mol%HfC-SiC embedded powder; the mass ratio of the anhydrous ethanol to the raw material powder is 3:1; the grinding balls are zirconia ball milling beads; the diameters of the zirconia ball milling beads are 2 mm, 5 mm and 8 mm, respectively; the mass ratio of the 2 mm, 5 mm and 8 mm zirconia ball milling beads is 1:2:1; and the ball-to-material ratio is 8:5.

[0074] (2) The carbon-based composite material is embedded in the TaC-20mol% HfC-SiC embedding powder obtained in step (1), and then placed in a graphite crucible, heated to 1800°C at 10°C / min in an argon atmosphere, and pressurelessly sintered for 3 hours to obtain a TaC-20mol% HfC-SiC ceramic coating based on the carbon-based composite material with a thickness of 170±20μm.

[0075] The Ta based carbon-based composite material obtained in Example 1 of the present invention was heated by an oxyacetylene flame at a temperature of 2200°C. 0.8 Hf 0.2 The C-SiC ceramic coating was ablated for 120 seconds, and its ablation performance parameters are shown in Table 1.

[0076] Table 1 Ta based on carbon-based composite material obtained in Example 1 0.8 Hf 0.2 Ablation Performance Data Sheet of C-SiC Ceramic Coating

[0077]

[0078] It can be seen from Table 1 that the Ta based carbon-based composite material obtained in the embodiment 0.8 Hf 0.2 The mass ablation rate of C-SiC ceramic coating is 8.3×10 -4 g / s, the linear ablation rate is 1.5×10 -4 mm / s, indicating that the Ta based on the carbon-based composite material obtained by the present invention 0.8 Hf 0.2 C-SiC ceramic coating has good resistance to oxidation and ablation.

[0079] The Ta prepared in Example 1 was examined by scanning electron microscopy. 0.8 Hf 0.2 The morphology of C ceramic powder is characterized, such as Figure 1 As shown in the figure: 0.8 Hf0.2 The powder particles in the C ceramic powder have obvious agglomeration and are tightly packed. If we further zoom in, we can see that each agglomerate is composed of a large number of secondary particles with smaller particle sizes.

[0080] The Ta prepared in Example 1 was analyzed by energy spectrometer. 0.8 Hf 0.2 C ceramic powder was analyzed and the results are as follows Figure 2 As shown in the figure: 0.8 Hf 0.2 The secondary particle size of C ceramic powder is mainly concentrated in 1~3μm, Ta 0.8 Hf 0.2 The three elements Ta, Hf and C are evenly distributed in a single grain of C ceramic powder, and no element segregation occurs.

[0081] The Ta prepared in Example 1 was analyzed by X-ray diffractometer. 0.8 Hf 0.2 The physical phase of C ceramic powder was analyzed. Figure 3 As shown in the figure: 0.8 Hf 0.2 The diffraction peak of the TaC ceramic powder shows a highly crystalline single-direction diffraction feature, without any residual oxides and amorphous carbon; this indicates that the lattices of TaC and HfC diffuse into each other during the heat treatment process to form TaC. 0.8 Hf 0.2 The diffraction peak of C.

[0082] The Ta based carbon-based composite material obtained in Example 1 was examined by scanning electron microscopy. 0.8 Hf 0.2 The surface morphology and phase of C-SiC ceramic coatings were characterized, such as Figure 4 As shown in the figure: Figure 4 The right picture shows that Ta based on carbon-based composite materials 0.8 Hf 0.2 The surface of C-SiC ceramic coating is mainly composed of black SiC phase and white Ta 0.8 Hf 0.2 C phase, and Ta 0.8 Hf 0.2 C is evenly distributed among SiC.

[0083] The Ta based carbon-based composite material obtained in Example 1 was examined by scanning electron microscopy. 0.8 Hf 0.2 The cross-sectional morphology of the C-SiC ceramic coating was characterized, such as Figure 5 As shown in the figure: Ta based on carbon-based composite materials 0.8 Hf 0.2The molten Si in the C-SiC ceramic coating penetrates into the carbon-based composite material, forming an embedded interlocking structure at the interface, forming a strong bond with the carbon-based composite material; and the coating presents a continuous and dense structure with a thickness of 20 to 170 μm.

[0084] The Ta based carbon-based composite material obtained in Example 1 of the present invention was heated by an oxyacetylene flame at a temperature of 2200°C. 0.8 Hf 0.2 The C-SiC ceramic coating was ablated for 120s. Its macroscopic morphology and ablation test curve are shown in the figure below. Figure 6 and Figure 7 As shown. Figure 6 It can be seen that the Ta based on carbon-based composite material obtained in Example 1 0.8 Hf 0.2 After the C-SiC ceramic coating was tested at 2200℃ for 120s by oxyacetylene flame, the coating was uniform and had no cracks. Figure 7 It can be seen that the timing principle of ablation test is to start timing after the temperature reaches 2200℃, and the ablation time is 120s.

[0085] The Ta based carbon-based composite material obtained in Example 1 was examined by scanning electron microscopy. 0.8 Hf 0.2 The cross-sectional morphology and phase of the C-SiC ceramic coating after ablation were characterized, such as Figure 8 As shown in the figure, the carbon-based composite material Ta obtained in Example 1 0.8 Hf 0.2 After the C-SiC ceramic coating was ablated by oxyacetylene flame at 2200℃ for 120s, the coating was uniform and dense, and was well bonded to the substrate, with no signs of peeling between the coating and the substrate.

[0086] The TaC-20mol% HfC-SiC ceramic coating based on the carbon-based composite material obtained in Comparative Example 1 of the present invention was ablated for 120s using an oxyacetylene flame at a temperature of 2200°C. The macroscopic morphology thereof is shown in FIG. Fig. 9 As shown in the figure, it can be seen that after the TaC-20mol% HfC-SiC ceramic coating based on the carbon-based composite material obtained in Comparative Example 1 was tested at 2200°C for 120s by an oxyacetylene flame, the coating was burned through, exposing the carbon-based composite material.

[0087] The surface morphology of the TaC-20mol% HfC-SiC ceramic coating based on the carbon-based composite material obtained in Comparative Example 1 after ablation was characterized by a scanning electron microscope. Fig.10 As shown in the figure, it can be seen that the TaC-20mol% HfC-SiC ceramic coating based on the carbon-based composite material obtained in Comparative Example 1 was burned through after being subjected to an oxyacetylene flame ablation test at 2200°C for 120s.

[0088] The surface morphology of the TaC-20mol% HfC-SiC ceramic coating based on the carbon-based composite material obtained in Comparative Example 1 after ablation was characterized by a scanning electron microscope. Fig.11 As shown in the figure, it can be seen that the TaC-20mol% HfC-SiC ceramic coating based on the carbon-based composite material obtained in Comparative Example 1 was burned through after being subjected to an oxyacetylene flame ablation test at 2200°C for 120s.

[0089] In summary, the carbon-based composite material Ta prepared by the present invention 0.8 Hf 0.2 C-SiC ceramic coating has good ablation resistance and does not crack.

[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a TaHfC-SiC ceramic coating based on a carbon-based composite material, comprising the following steps: (1) ball milling a raw material powder to obtain an embedded powder; the raw material powder comprises TaHfC ceramic powder, Si powder and C powder; (2) embedding the carbon-based composite material into the embedding powder obtained in step (1) and sintering the embedded powder to obtain a TaHfC-SiC ceramic coating based on the carbon-based composite material.

2. The preparation method according to claim 1, characterized in that: The particle size of the TaHfC ceramic powder in the step (1) is 1 to 3 μm.

3. The preparation method according to claim 1, characterized in that: The preparation method of the TaHfC ceramic powder comprises: ball milling and sintering Ta2O5 powder, HfO2 powder and C powder in sequence to obtain TaHfC ceramic powder.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step (1), the mass content of TaHfC ceramic powder in the raw material powder is 30-40% of the mass of the raw material powder.

5. The preparation method according to claim 1, characterized in that: In the step (1), the mass content of Si powder in the raw material powder is 40-50% of the mass of the raw material powder.

6. The preparation method according to claim 1, characterized in that: In the step (1), the mass content of C powder in the raw material powder is 5-10% of the mass of the raw material powder.

7. The preparation method according to claim 1, characterized in that: In the step (1), the rotation speed of the ball mill is 300-500 r / min, the time of the ball mill is 4-6 hours, and the medium of the ball mill is anhydrous ethanol.

8. The preparation method according to claim 1, characterized in that: In the step (2), the sintering temperature is 1600-1800° C., and the sintering time is 1-3 hours.

9. The preparation method according to claim 1 or 8, characterized in that: The sintering in step (2) is pressureless sintering, and the sintering atmosphere is an inert atmosphere.

10. The TaHfC-SiC ceramic coating based on carbon-based composite material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The invention comprises a carbon-based composite material and a TaHfC-SiC ceramic coating which is in-situ generated on the surface of the carbon-based composite material.

Citation Information

Patent Citations

  • Preparation method for HfC-SiC coating on C / C composite material surface

    CN105541416A

  • C / C composite material superhigh temperature ceramic coating, and preparation method thereof

    CN108530110A

  • Carbon / carbon composite material surface (HfZrTi) C3 medium-entropy carbide ablation-resistant coating and preparation method thereof

    CN114853506A